PENGARUH GENDER, DAYA TARIK PROMOSI, KEPEMILIKAN KARTU KREDIT TERHADAP PERILAKU PEMBELIAN IMPULSIF ONLINE PRODUK LIFESTYLE - Putra, Made Santika; Santika, I Wayan (E-Jurnal Manajemen; Vol 7 No 10 (2018)DO - 10.24843/EJMUNUD.2018.v07.i10.p13, 2018)
Technological advances create a new paradigm in the business world. The rapid development of internet usage will have a positive impact for online business in Indonesia. One of the most desirable consumer behavior by marketers who use online media is the impulsive purchase behavior. This study aims to determine the effect of gender, attractiveness of promotion and ownership of credit cards against impulsive buying behavior online. This research was conducted in Denpasar City involving 60 respondents through purposive sampling method. This method was chosen because it is not known exactly the number of population. Data were collected through questionnaires. Data analysis technique used is multiple linear regression analysis technique.The results of this study found that gender positively and positively affects online impulsive buying behavior, promotional appeal positively and significantly affects online impulsive buying behavior and credit card ownership positively and significantly affects online impulsive buying behavior. Marketers are expected to be more accurate in determining market segmentation, more creative in promoting and able to provide convenience and convenience in the payment process when shopping online. Keywords: gender, attraction of promotion, credit card ownership, impulsive buying behavior.